Alnarps rehabiliteringsskog : ett gestalningsförslag - Sydow, Nils von (SLU/Southern Swedish Forest Research Centre, 2008)
The understanding of the role of nature for rehabilitation of both physical and psychological afflictions has greatly increased in the last few years. There's a lot of science that describes the healing effects of nature. The rehabilitation garden in Alnarp has contributed with very positive results from the treatments of patients with burnout syndrome. In the first stages of rehabilitation, the need for calm is very important and a demand-less and stress-free environment is of essence. From this need rises a suggestion of a rehabilitation forest to be planted in connection to the present gardens. The work process started with literature studies concerning the subject which has been supplemented with phone calls, study visits and lectures. The result has been presented to the chief of the gardens after meetings with the supervisors whereupon the result has been adjusted. The forest area is inspired by the four park characteristics the calm, the biodiverse, the wild and the spacious. The four characteristics will together contribute to the right atmosphere for the first stages of rehabilitation. The forest will consist of three different zones with a varied tree composition and structure to attract as wide audience as possible. In the first zone, where the ground level is at its lowest, a small lake will be constructed. The forest in this zone will be dominated by alder, aspen and birch and the ground vegetation will be rich. The material from the lake excavation will be used to construct a small hill in the middle of the area which will make a fine resting place with easy access to the tree zones of the forest. Old fruit trees are left in the second zone with a mixture of mostly aspen and birch. The forest will be bright with a lighter canopy. In this part of the area, the ground level is at its highest and an artificial spring will start the small stream that creeps down towards the lake. The third zone will be the most mixed one with an even distribution among the species and will border to a small meadow that slopes towards the lake. Generally the three zones have a fast growing canopy to fast get the "forest feeling". The "noble" broadleaves will grow into the canopy from below and the fast growing trees can be taken out continuously for the desired structure and species composition. Between the zones there will be transition zones where the composition in tree species is mixed from both bordering zones to make as smooth transition as possible to avoid the feeling of division. The forest is supposed to give the feeling of a rich and flourishing grove, typical for southern Sweden. There will be a lot to se and smell to stimulate the senses. The forest edge will be dense for a rich bird life and there will be plenty of flowers and berries, both in bushes and trees.